PENGEMBANGAN KURIKULUM PAI BERBASIS KEMAJEMUKA - Moh Kamilus Zaman (Fakultas Tarbiyah, Universitas Ibrahimy, 2019)
Social and development change requiring changes and developments in education curriculum.The dynamics of diversity in this country leads to nation disintegration which insists national education and institutions respond quickly for NKRI’s wholeness, because sometimes radical movements and thoughts on behalf of Islam. In relation with this problem, there are three steps in curriculum development that can be offered in this article, they are development of educational goals, materials or contents, and institutions